IOT based Garbage Management System - Dhamde, Vedant; Pacholi, Ameya; Ragit, Shreyas; Agrawal, Heena (International Journal of Computer Sciences and Engineering, 2025)
Garbage management is a major issue for almost every country, developing or developed alike. Innumerable garbage bins and dust bins are left unattended due to lack of management which leads to unhygienic conditions and creates an unhealthy environment. It could also result in spread of diseases and illnesses. To avoid such problems, we have designed an "IOT Based Garbage Management System". The main idea of this system is to discern whether the garbage bin is full or not in order to make efficient use of time and man-power by providing instant cleaning of the dustbins. Arduino UNO, interfaced with the ultra-sonic sensor is mounted on every garbage bin which checks the level of the garbage in the bin and sends the alert signal to the municipal web server forthwith if the garbage bin fills up to a set minimum threshold level. After cleaning the dustbin, the status of the bin is automatically set to empty in the municipal web server. The whole process contains an embedded module integrated with RFID and IOT facilitation.Also, the real time status of how much garbage has been filled can be monitored by a municipal authority which controls the system. We have also developed an android application which will be linked to the municipal web server to notify the alerts from the microcontrollers to the driver to take necessary action thereby reducing the manual process of monitoring and verification. The notifications are sent to the android application available to the driver.[1,2]